1986
DOI: 10.1515/jpme.1986.14.5.299
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy complicated by diabetic nephropathy

Abstract: Diabetes mellitus is a high risk complication of pregnancy and this is particularly true whenever long standing diabetes is complicated by diabetic nephropathy. Five cases are reported of diabetic pregnancy complicated by nephropathy. Four women delivered healthy babies, and one patient aborted spontaneously in the 9th week of gestation. It is suggested that first and foremost in complicated diabetic pregnancy strict normoglycemia should be adhered to prior and all through pregnancy. Our findings based on thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Similar results to Kitzmiller et al were found by Dicker et al 33 in five patients of White class F in which diabetic nephropathy was diagnosed in the first trimester. In these patients creatinine clearance did not change during gestation, whereas 24-hour protein excretion increased in all patients.…”
Section: Diabetic Nephropathysupporting
confidence: 90%
“…Similar results to Kitzmiller et al were found by Dicker et al 33 in five patients of White class F in which diabetic nephropathy was diagnosed in the first trimester. In these patients creatinine clearance did not change during gestation, whereas 24-hour protein excretion increased in all patients.…”
Section: Diabetic Nephropathysupporting
confidence: 90%
“…Therefore, in women with well-controlled diabetes who do not have nephropathy or other advanced vascular complications their decision about whether or not to have children will largely be influenced by factors not associated with diabetes itself. In contrast, for women with diabetic nephropathy (who in most cases also have proliferative retinopa- death, c Significantly different at thy) concern about fetal and maternal complications remains a major issue [1][2][3]. Despite substantial improvements in perinatal survival with normoglycaemic control, treatment of hypertension and modern methods of assessment of fetal well-being and perinatal care, there is still a high rate of fetal morbidity largely due to prematurity [3].…”
mentioning
confidence: 99%
“…According to four previous reports, the fetal outcome of pregnancies for mothers with diabetic nephropathy has substantially improved since the 1970's compared to the 1960's when perinatal survival rates were below 70 % [1][2][3][5][6][7]. In our series of 36 pregnancies of 29 mothers there were no perinatal or intrauterine deaths but prematurity and associated perinatal morbidity was considerably higher than in pregnancies of diabetic women without nephropathy.…”
Section: Discussionmentioning
confidence: 66%
“…Age (years) Duration of diabetes (years) Planned pregnancies (n) Women with irregular menstrual periods (n) Gestations/primipari (n) Initial visit to diabetic pregnancy clinic (gestational week) Elective abortion for medical reasons (n) thy) concern about fetal and maternal complications remains a major issue [1][2][3]. Despite substantial improvements in perinatal survival with normoglycaemic control, treatment of hypertension and modern methods of assessment of fetal well-being and perinatal care, there is still a high rate of fetal morbidity largely due to prematurity [3].…”
Section: With Nephropathy Without Nephropathy Pregnancies~women (N)mentioning
confidence: 99%